April im Oktober : ein kleiner Roman - Werfel, Franz, 1890-1945.
Holograph manuscript (in German) of Werfel's novel. Includes a TLS (1941 July 6) from Werfel to Joseph Auslander regarding the gift of his manuscript to the Library of Congress.
Author.
Collection material in German, with English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Austrian literature; Authors